Atlantic Crossings. Intellectual-Politicians and the Diffusion of Corporatism in the Thirties Latin America - Pinto, Antonio Costa (2020)
In this chapter I deal with the main transnational agents of diffusion of corporatism in Latin America, giving particular salience to the Catholic Church, and the main intellectuals and intellectual-politicians that introduced and developed corporatist proposals. The concept of intellectual-politician will be used here to define those intellectuals who were participating in the institutional crafting of these regimes as formal or informal members of the decision-making elite (i.e. as advisers, deputies, cabinet members or party leaders). They provided space for interaction among politicians and the transnational intellectual arena, cementing ideological and political relations and models